Pendampingan Produk Home Industry “Sale Pisang Bu Mul” di Desa Tugurejo, Ponorogo melalui Rebranding, Repackaging, dan Digital Marketing - Al Faruqi, Achmad Reza Hutama; Muhammad, Emyr; Setyowati, Nur Iman Siyus; Gattusso, Gagah; Nurhanif, Senna Zulsyaikh; Oktavian, Muhammad Iqbal; Putra, Surya Andhika; Irawan, Feri; Mahendrata, Dwi Yuda; Budiman, Ihsan; Philbertha, Regan Azzaria (Civiliza Publishing, 2025)
The development of digital marketing and branding strategies is essential for small businesses to compete in today’s market. This study aims to enhance the competitiveness of Sale Pisang Bu Mul, a home industry product from Tugurejo, Ponorogo, by optimizing branding, packaging, and digital marketing strategies. The participatory approach was employed in this community service program, involving direct mentoring, training, and evaluation. The mentoring focused on three key aspects: digital marketing implementation, e-commerce utilization, and packaging improvement. The results indicate a significant increase in product visibility and consumer engagement through social media and online marketplaces. The new packaging design has enhanced consumer appeal and product trust, contributing to improved market reach. By leveraging digital platforms, Sale Pisang Bu Mul has successfully expanded beyond its local market. This initiative demonstrates that digital marketing and effective branding play a crucial role in strengthening small businesses' competitiveness. Future developments should focus on continuous digital innovation and maintaining product quality to sustain business growth. Furthermore, this mentoring model can be replicated for other small businesses to expand their market reach and improve economic sustainability.